Peningkatan Peran Pembudidaya Perempuan Dalam Budidaya Dan Optimalisasi Hasil Panen Rumput Laut Di Kabupaten Buton Utara - Kasim, Maruf; Sudia, La Baco; Nurdiana; Jalil, Wardha (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Seaweed is a leading commodity that can provide a good selling value. Current seaweed cultivation methods are experiencing very serious problems. Some of these problems include; low production and harvest yields caused by large amounts of seaweed broken and washed away during the cultivation periods, attacks by fish and turtle pests that graze seaweed, and frequent environmental changes that are detrimental to seaweed farmers. Cultivation is generally carried out by men because the longline method is difficult for women. The Horizontal Net innovation is a tool that is women-friendly, environmentally friendly, and production-friendly. Community service activities are carried out in North Buton Regency by providing training and implementation of horizontal net use to female farmers. To increase harvest yields and the selling value of dried seaweed, LPPM UHO in collaboration with Bappeda and Dekranasda North Buton Regency, fully supported by the Ministry of Higher Education, Science, and Technology, held training on diversification of processed products from seaweed. Products trained include the manufacture and packaging of seaweed jam, sticks, and seaweed jelly drinks. Training in making horizontal nets and various foods from seaweed provides new hope for increasing seaweed production and sales value for female seaweed farmers in North Buton Regency, Southeast Sulawesi Province